Partisipasi Siswa dalam Quantum Wiriting: Sebuah Studi Pembelajaran Menulis pada Siswa Kelas XII SMAN di Kabupaten Sekadau - Kusnadi Kusnadi (PT. Media Edukasi Borneo, 2021)
The purpose of this study was to describe an increase in the ability to write job application letters through the Quantum Writing method in Class XII SMAN students in Jongkong. This type of research was classroom action research. The subjects in this study amounted to 35 people which were carried out in 2 cycles. Data collection techniques consisted of observation and tests. The procedures used were (1) planning, (2) implementation, (3) observation, (4) reflection. The results of this study indicated it can improve learning activities. This can be seen from the teacher's activities in the first cycle obtained an average of 27.5 with